(untitled) (Biological Sciences - PJSIR, 2024)
The present histopathological study was conducted to reveal the ameliorative potential of Syzygium cuminin and Morus nigra fruit extracts in response to hexavalent chromium Cr (VI) induced renal toxicity. Mice were divided into four study groups i.e., control (Ctl) group, chromium (Cr) treated group that was given 50 ppm chromium given ad labitum for 10 days, chromiun+Jambul group (Cr+Jb) given 50 ppm (Cr) for 10 days followed by 0.2mL/12 h of fresh Jambul fruit extract for 5days and chromium+Morus (Cr+Mr) group given 50ppm (Cr) for 10 days followed by 0.2mL/12 h of fresh Morus fruit extract for next 5 days. For renal histopathological study kidney was recovered on 15th day of study. In Cr (VI) group, the glomeruli are rounded and highly stained along with t atrophy and necrosis in Cr group including tissue damages i.e. shrinkage along with peripheral fibrosis of the renal glomeruli and fairly large number of glomerular obliterations. In Cr+Jb and Cr+Mr group, rapid reversal of the nephropathological signs. The inter-tubular spaces were reduced and renal tubules regained the size in Cr+Jb and Cr+Mr group just like Ctl. These findings suggest that Cr is potentially toxic for animal kidney. Highest mean value for CSA of cortical glomeruli was found in Cr+Jb (3132.5± 266.9µ2) and CSA of medullary glomeruli was (3129.1±145.2µ2) as compared to cortical Ctl glomeruli (2441.7± 95.7µ2) & cortical Ctl glomeruli (2515.1.7±115.1µ2). However, such pathologies can rapidly be repaired upon Syzygium cumini and Morus nigra. pulp extract treatment. Thus it is clearly indicated that Morus nigra fruit extract possesses considerable excellent rescuing capacity against renal pathology of environmental toxins specifically Cr.